2019
DOI: 10.3390/ijerph16050808
|View full text |Cite
|
Sign up to set email alerts
|

Using Human Movement Data to Identify Potential Areas of Zika Transmission: Case Study of the Largest Zika Cluster in Singapore

Abstract: Singapore experienced its first Zika virus (ZIKV) cluster in August 2016. To understand the implication of human movement on disease spread, a retrospective study was conducted using aggregated and anonymized mobile phone data to examine movement from the cluster to identify areas of possible transmission. An origin–destination model was developed based on the movement of three groups of individuals: (i) construction workers, (ii) residents and (iii) visitors out of the cluster locality to other parts of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…This category comprises mobile phone signals. 4 [ 84 87 ] Simple mobile communication Simple mobile phone communication involves the use of mobile phone numbers to allow contact with others including voice communication (e.g. calls).…”
Section: Resultsmentioning
confidence: 99%
“…This category comprises mobile phone signals. 4 [ 84 87 ] Simple mobile communication Simple mobile phone communication involves the use of mobile phone numbers to allow contact with others including voice communication (e.g. calls).…”
Section: Resultsmentioning
confidence: 99%
“…Another recent study conducted by Huang [57] used weekday commuting network to construct an algorithm to analyze the diffusion of two infectious diseases in Taiwan, and the result suggested the availability of the commuting network in predicting epidemic diseases. Besides, Rajarethinam [17] conducted a study about Zika epidemic in Singapore using mobile phone data and found that there were higher odds of Zika cases being reported in the areas that were visited by people from epidemic clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the meteorological environment, social-economic environment, and built environment could facilitate local infections [7][8][9][10][11][12][13][14][15]. Due to the limited flight range of mosquitos, which is usually less than 400 m [16], human mobility is considered and proven to be another important driver for DF transmissions [16][17][18][19][20][21][22][23][24][25]. Therefore, understanding human mobility is key to controlling the spread of infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies using mobile phone tracking data through CDR and mobile phone signals have been conducted in Asia region (Wesolowsiki et al, 2015;Mao et al, 2016;Rajarethinam et al, 2019). This strategy, mobile phone tracking data -when integrated with disease surveillance data and environmental data-has the potential to estimate human mobility in order to predict the spread of arbovirus diseases and outbreaks.…”
Section: Outcome Dimensionsmentioning
confidence: 99%